TANTANGAN KERJASAMA TRIANGULAR ANTARA INDONESIA-KOICA-UNDP DALAM PROYEK ACCELERATING CLEAN ENERGY ACCESS TO REDUCE INEQUALITY (ACCESS) TAHUN 2020-2022 - Christinna Fransisca Theresia, (2023)
This study describes the challenges of triangular cooperation between Indonesia, KOICA, and UNDP in building solar power plants in 23 remote villages in Indonesia during the period 2020-2022. In this study, it is explained why the ACCESS project cooperation in Indonesia is referred to as triangular cooperation using the concept of understanding triangular cooperation proposed in the Nairobi outcome document of the High-Level United Nations Conference on South-South Cooperation (A/RES/64/222). The purpose of this study is to determine the factors that become challenges in triangular cooperation, especially in the field of new renewable solar energy in underdeveloped areas in Indonesia. The author uses descriptive qualitative research methods with primary and secondary data sources. The data collection technique that the author uses is to use interviews and literature studies. The author uses qualitative data analysis techniques in conducting data analysis which will later be associated with theories and concepts as an analytical reference. The findings of this study are that there are challenging factors in global economic conditions due to Covid-19 and social restrictions during the Covid-19 pandemic which limit the space for project managers to realize the construction of PLTS on target.